Critical Success Factors for the Better Performance of Agricultural Marketing Co-operative Societies in Rombo District, Tanzania: Are Members Aware of Them? - Victor Shirima (Cogent Business & Management, 2022)
The purpose of the study was to establish the Critical Success Factors (CSFs) for the primary Agricultural Marketing Co-operatives Societies (AMCOS) at Rombo District in Tanzania. Specifically, the study aimed to establish factors that members perceive to be critical to their success, and to assess their contribution to the AMCOS performance. The study identified factors through intensive literature review, then refining them before testing them through survey to members and employed survey by distributing 334 questionnaires to members to the AMCOS that have the autonomy to do business directly without dependingon their umbrella institutions. Qualitative data were also used in order to validate the quantitative data. Data from survey were analysed by factor analysis in order to have factors which were mostly accepted by the AMCOS members. After categorising the factors obtained from the factor analysis, regression analysis was conducted to assess their influence on the performance. Qualitative data were analysed using content Analysis by the help of ATLAS Software. The study established Eleven (11) CSFs that were categorised into: commitment (use of personal skills, members' control and promotion), governance (measurement system, governance structure, leadership support, and transparency), strategy (self-evaluation, objective development, strategy focused, living the vision of the institution). The study found the CSFs to have positive significant influence on the primary AMCOS performance. The study concludes that members of the primary AMCOS do have their common factors which they believe to be key for the success of their institutions, that affect positively the performance of their cooperatives. The study recommends that, the CSFs suggested by the members should be given priority in any decision that is intended to affect the cooperatives that can be easily translated according to their expectations to have strong institutions.
Keywords: 650; Co-operative; Commitment; Critical Success Factors; Governance; performance; Strategy